SEJARAH KODIFIKASI SUNNAH: Telaah Historis Abad III dan IV H - Asnan Purba (LPPM IAIN Kediri, 2022)
This article aims to examine the codification of the Sunnah by focusing on studies in the 3rd and 4th centuries H, because this is an important phase of the process of bookkeeping sunnah or hadith. The compilation of hadith during the time of the Companions was not significant, because they still focused on the compilation of the Qur'an. Companions are also afraid that the verses of the Qur'an and Al-Hadith will be mixed up if they are recorded at the same time. Many of the Companions still memorized the Hadith of the Prophet, so the tradition of spreading it was in oral form. The need to immediately codify the hadith is increasingly urgent because during the Tabi'in period many fake traditions circulated, especially with political tendencies. This research is a library research with a chronological-historical approach. The results of the study indicate that the codification of hadith at this time took place massively on the initiative of Caliph Umar bin Abdul Aziz of the Umawiya Dynasty and the results of its performance can still be felt today. Artikel ini bertujuan untuk menelaah kodifikasi Sunnah dengan menggunakah pendekatan historis. Penulis menitik beratkan kajian ini pada rentang waktu abad ke-3 dan 4 H, karena pada masa ini adalah fase penting dari proses pembukuan sunnah atau hadis. Penyusunan hadis pada masa Sahabat belum signifikan, karena mereka masih memfokuskan perhatian pada penyusunan Al-Quran. Sahabat juga takut akan bercampurnya antara ayat-ayat Al-Qur'an dan Al-Hadis jika dibukukan dalam rentang waktu yang bersamaan. Para sahabat masih banyak yang hafal dengan Hadis-hadis Nabi, sehingga bentuk penyebarannya hanya dalam bentuk lisan. Kebutuhan untuk segera mengkodifikasi hadis semakin mendesak karena pada masa Tabi’in banyak beredar hadis-hadis palsu dengan tendensi politis. Penelitian ini masuk dalam kategori kajian pustaka (library research) dengan pendekatan kronologis-historis. Hasil penelitian menunjukkan bahwa kodifikasi hadis pada masa ini berlangsung secara massif atas prakarsa Khalifah Umar bin Abdul Aziz dari Dinasti Umawiyah dan hasil kinerjanya masih bisa dirasakan sampai saat ini.